Emerging biomarkers for improving pregnancy planning in multiple sclerosis - Cuello, Juan Pablo; Meldaña Rivera, Ariana; Monreal, Enric; Gómez Lozano, Ana; García Cano, Ana Maria; García Domínguez, Jose Manuel; Fernández Velasco, José Ignacio; Costa-Frossard França, Lucienne; Goicochea, Haydee; Higueras, Yolanda; De León-Luis, Juan Antonio; Sainz De La Maza, Susana; et al. (Frontiers in Neurology, 2024)
Background Patient disability, relapse rate, and age are used for family planning in multiple sclerosis (MS). However, the need for more accurate biomarkers is widely recognized. We aimed to explore the influence of age on neurofilament light chain (sNfL), which reflects acute inflammation; glial fibrillary acidic protein (GFAP), associated with disability progression independent of relapses; and anti-Müllerian hormone (AMH), reflecting ovarian reserve, to provide a tailored family planning strategy. Methods This case-control study included 95 MS patients and 61 healthy control women (HCW). sNfL and GFAP levels were measured using a sensitive single-molecule array assay. AMH levels were measured by the automated Elecsys® Anti-Müllerian Hormone Assay. Results We observed no significant differences in AMH values between MS patients and the control group within any of the age-matched categories. Age exhibited a negative correlation with AMH values in both groups, as expected. Nevertheless, our findings suggest a slight tendency toward reduced ovarian reserve in MS patients (rho MS patients = −0.67, p < 0.0001; rho HCW = −0.43, p = 0.0006). Interestingly, among the 76 MS participants under 40 years old, we identified ten individuals (13.1%) with AMH levels below 0.7 ng/ml, indicative of a low ovarian reserve, and an additional six individuals (7.8%) with AMH levels between 0.7 ng/ml and 0.9 ng/ml, suggesting a potential risk of premature ovarian failure. Conversely, sNfL and GFAP levels in the MS group exhibited high variability but showed no significant association with age intervals. Conclusion We found no significant differences in AMH, sNfL or GFAP values between MS patients and the control group within any of the age-matched categories. The assessment of AMH, sNFL and GFAP levels at MS onset facilitates personalized therapeutic and family planning strategies for childbearing-age women.